IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA DI DESA MALALA KECAMATAN DONDO KABUPATEN TOLITOLI - Sarifudin, Sarifudin (Katalogis, 2014)
This studi aimed to find out and describe the implementation of village budget allocationpolicy in Malala village, Dondo district, Tolitoli regency and several aspects than influenced its implementation. This study was carried out in Malala village, Dondo district, Tolitoli regency. The informants with 9 people were selected by using purpossive sampling technique, adopted from the theory of Van Meter and Van Horn. This was descriptive qualitative research method. Technique of data collection dealt with observation, interview and documentation. The research result showed that the implementation of the policy has not portrayed the ideal condition related to performance policy and the public expectation with several regulations to organize its implementation. Based on the policy implementation model of Van Meter and Van Horn as the grand theory to analyze problem, the research result can be concluded that there were some aspects that influenced the implementation based on the fact in the filed, namely : 1). standard and aim of the policy have not been done properly and achieved well; 2). human resources still need to be organize and improved;3). the characteristics of organization executors have not seemingly understood the main job and function; 4). the attitudes of the activity executors have not been paid attention toward if they found problems in the field; 5). Communication among related organization has not been effective and the socialization intensity has not been done from government of the regency to villagers as the targeted groups; and 6). related to the aspects of social, economic, and politic environment, the social and economic aspects of public still dominate and influence the condition of public life that becomes the target of the policy.